Interaction between Ukrainian Nationalists Organizations of Canada with Ukrainian nationalist movement at Home and in the World (1918–1939) - Dzyra, Olesia (Київський національний університет імені Тараса Шевченка, 2018)
The article briefly reports about the process of founding and development of the Ukrainian nationalist movement in the Diaspora in Canada in interwar period, which was presented by Ukrainian war veterans association and Ukrainian national federation, and characterizes directions of their activity. In this context it the emphasis has been made on the relief activities of these organizations to compatriots at home in the time of famine, repression, the rise of the national liberation struggle. It has been researched the connections of these organizations with other nationalist societies in the world. For example, Ukrainian nationalists of Canada were in contact with the Organization for the Rebirth of Ukraine from the USA, and in Europe – with the Ukrainian national association in Paris, Ukrainian military organization, and later – with the Organization of Ukrainian Nationalists and others. The results of such relations and cooperation for the Ukrainian nationalist movement in Canada and the Ukrainian nation have been analyzed.Keywords: Nationalist Movement, Public Organization, Ukrainian War Veterans Association, Ukrainian National Federation, Interaction of Ukrainians in the World.

Дзира ОлесяДосліджено процес зародження та розвитку українського націоналістичного руху в діаспорі Канади у міжвоєнний період, який був представлений Українською стрілецькою громадою та Українським національним об’єднанням. Проаналізовано допомогову діяльність націоналістів по відношенню до своїх співвітчизників на Батьківщині. Охарактеризовано їхні зв’язки з іншими націоналістичними організаціями у світі та в Україні.Ключові слова: націоналістичний рух, громадські організації, стрілецька громада, Українське національне об’єднання, взаємодія світового українства.
Взаємодія українських націоналістичних організацій Канади з українським націоналістичним рухом на Батьківщині й у світі (1918–1939)